1995
DOI: 10.2307/2269359
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Native Insect as a Biological Control for an Introduced Weed

Abstract: We have evaluated the potential of a North American aquatic weevil, Euhrychiopsis lecontei, to serve as an agent of biological control for an exotic weed, Eurasian watermilfoil (Myriophyllum spicatum), which is currently found throughout much of the United States and in some southern provinces of Canada. We have found this weevil on M. spicatum in lakes where populations of the exotic weed have declined. We introduced weevils into enclosures in two lakes dominated by M. spicatum. In both lakes there was 50% le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 39 publications
1
35
1
Order By: Relevance
“…In less than 11 years, however, a native weevil (Euhrychiopsis lecontei) has formed incipient host races on M. spicatum (Sheldon and Jones 2001). High abundances of the weevil have been associated with large declines of M. spicatum within lakes, and laboratory tests have shown that the weevil can have a significant impact on the growth of M. spicatum although, interestingly, not M. sibiricum (Sheldon and Creed 1995).…”
Section: Population Regulation and Life History Evolutionmentioning
confidence: 99%
“…In less than 11 years, however, a native weevil (Euhrychiopsis lecontei) has formed incipient host races on M. spicatum (Sheldon and Jones 2001). High abundances of the weevil have been associated with large declines of M. spicatum within lakes, and laboratory tests have shown that the weevil can have a significant impact on the growth of M. spicatum although, interestingly, not M. sibiricum (Sheldon and Creed 1995).…”
Section: Population Regulation and Life History Evolutionmentioning
confidence: 99%
“…Previous studies have shown that native parasites can limit exotic invaders escaping from their natural enemies and have fewer negative effects on nontarget species (Sheldon and Creed 1995;Torchin and Mitchell 2004;Krakau et al 2006;Lian et al 2006;Mitchell et al 2006). Research has been dominated by laboratory studies.…”
Section: Introductionmentioning
confidence: 99%
“…Little is known about freshwater host choice (Newman 1991) and our work with the weevil Euhrychiopsis lecontei Dietz (=Eubrychiopsis lecontei), which has expanded its host range to include Eurasian watermilfoil Myriophyllum spicatum L. (e.g., Sheldon and Creed 1995;Solarz and Newman 1996;Newman et al 1997), suggests that freshwater specialist herbivores may respond to hostplants in ways similar to terrestrial insects. Determining the response to an exotic plant by this specialist herbivore will contribute to our understanding of herbivory in aquatic systems and to how specialist herbivores in both terrestrial and aquatic systems may respond to the introduction of exotic plant species.…”
Section: Introductionmentioning
confidence: 99%
“…The life history and basic ecology of the weevil have been described (Sheldon and Creed 1995;Newman et al 1996;Sheldon and O'Bryan 1996). All life stages are associated with the submersed plant, indicating that the weevil is fully aquatic.…”
Section: Introductionmentioning
confidence: 99%